THE MIDWIFERY CARE FOR PREGNANT WOMAN, MRS. A IN TEUBALUY VILLAGE, SUB-DISTRICT OF DARUL KAMAL, THE REGENCY OF ACEH BESAR: Midwifery Care for Pregnant Women - Nurul ummi; Satrinawati Berkat; Yusnaini Yusnaini (Journal of Midwifery and Community Health (JMCH), 2026)
The maternal mortality rate (MMR) remains a key indicator in assessing the quality of maternal healthcare. Comprehensive, high-quality antenatal care is essential for early detection of complications and for improved maternal and fetal health during pregnancy. This case report aims to provide midwifery care to a pregnant woman and document it in a midwifery SOAP note. The care was provided to Mrs. A, 37 years old, G2P1A0, at 27 weeks and 4 days of gestation in Teubaluy Village, Sub-district Darul Kamal, The regency of Aceh Besar. Subjective indicated that the mother had complained of back pain for the past week and had a history of cesarean delivery. Objective examination results indicated that the mother's and fetus's general condition was good, with blood pressure 120/80 mmHg, fetal heart rate 139 beats/minute, and hemoglobin level 13.6 g/dL. The midwifery care provided included education on pregnancy exercises to reduce back pain, recommendations for adequate rest, continued consumption of iron tablets, nutritional counseling, and education on pregnancy danger signs. Results of the care indicated that the mother understood the counseling provided and was able to reiterate the pregnancy exercise techniques taught. Comprehensive midwifery care is expected to increase maternal comfort during pregnancy and reduce the risk of complications.